KUALITAS PELAYANAN PENCATATAN AKTA NIKAH DI KANTOR URUSAN AGAMA KECAMATAN PALU BARAT - Nurhalizah, Sitti; Daswati; Mukarramah (JPS: Journal of Publicness Studies, 2025)
This study uses qualitative descriptive research, this study attempts to reveal accurate and factual facts systematically about marriage certificate registration services at the Palu Barat District Religious Affairs Office. This study uses the taliziduhu ndraha theory with 4 (four) indicators, namely, speed, accuracy, convenience, and fairness. Data collection techniques are carried out through field research including observation, interviews, and documentation. There are 6 informants in this study. Data analysis used is data collection, data condensation, data presentation and drawing conclusions. Based on the results of research conducted using the taliziduhu ndraha theory from 4 indicators of the accuracy aspect, it can be said that it is not optimal because there are still frequent delays, not on time to come to the office, for example, the SOP states that at 07.30 must be in the office but in reality employees often experience delays. Then the other 3 aspects have been running optimally, namely the aspects of speed, convenience, and fairness.